PENGARUH HARGA, PROMOSI, TEMPAT DAN KUALITAS LAYANAN TERHADAP PILIHAN PASIEN RAWAT INAP (Studi Kasus RS Yadika Group) - Didin Hikmah Perkasa (Universitas Mercu Buana, 2016)
The research was motivated by the number of visits patients hospitalized at the Hospital Group Yadikafluctuated and still not meet the targets set by management. This study aims to analyze the effect of pricing,promotion, place and quality of service to the selection of patients hospitalized at the Hospital Yadika Group. Collecting data in this study was conducted by questionnaire to 100 respondents inpatient hospitalYadika Group by using purposive sampling method to determine the responses to variable pricing, promotion, place and quality of service. Techniques of data analysis used were multiple linear regression analysis whichserves to prove the hypothesis of the study. Data that meets the test of validity, reliability testing, and testthe assumptions of classical processed so that the resulting regression equation as follows: Y = 3,204 + 0,389X1 + 0,226X2 - 0,009X3 + 0,187X4Based on the results obtained by the analysis of that variable pricing and service quality has a significant positive influence on the choice of inpatients in hospitals Yadika Group. Adjusted R square value of 0.619indicating that 61.9 percent of the variation in patient selection could be explained by four independentvariables in this study. While the rest of 38.1 percent is explained by other variables not examined in thisstudy.